2008
DOI: 10.1007/s10803-008-0642-y
|View full text |Cite
|
Sign up to set email alerts
|

When Asking Questions is Not Enough: An Observational Study of Social Communication Differences in High Functioning Children with Autism

Abstract: This investigation examined communication patterns between high functioning children with autism and their families and typically developing children and their families within traditional dinner time conversation. Twenty families with a child with autism (3.5-7 years.) and ten families with typically developing children (3.5-6 years) were video recorded during dinner and their interactions were coded. Results revealed that children with autism initiated fewer bids for interactions, commented less often, contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 23 publications
4
73
2
1
Order By: Relevance
“…Based on their difficulties in intuitive reading of social situations and of social partners' mental states, children with ASD also exhibit problems in initiating and maintaining conversations that are sensitive to the social context and to others' interests and previous knowledge (Jones & Schwartz, 2009;Paul et al, 2009). Especially limited are children's abilities to develop or expand interactions by taking turns within ongoing conversation or by switching topics to accommodate conversational partners' perspectives (Paul et al, 2009).…”
Section: Social Conversation In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Based on their difficulties in intuitive reading of social situations and of social partners' mental states, children with ASD also exhibit problems in initiating and maintaining conversations that are sensitive to the social context and to others' interests and previous knowledge (Jones & Schwartz, 2009;Paul et al, 2009). Especially limited are children's abilities to develop or expand interactions by taking turns within ongoing conversation or by switching topics to accommodate conversational partners' perspectives (Paul et al, 2009).…”
Section: Social Conversation In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Landa 2000). A recent observational study by Jones and Schwartz (2009) examined family dinnertime conversation for children with high-functioning ASD versus neurotypical children. They found that children with high-functioning ASD initiated fewer bids for interactions, responded less often to others' bids, and made fewer conversational exchanges.…”
mentioning
confidence: 99%
“…The unique characteristics of children who are diagnosed with Autism Spectrum Disorder (ASD) pose special challenges for those teachers and educators who serve them in the schools and for the caregivers who deal with them in a daily base (Howlin, 2006). Social communication is the core deficit of ASD in which is definedbroadly as an individual's ability to respond to social bids and initiates and maintain interactional discourse (Adamson, McArthur, Markov, et al, 2001;Bruinsma, Koegel, & Koegel, 2004;Jones & Schwartz, 2009). These impairments are typically manifested by difficulty in responding to verbal initiation exhibited by others, inappropriate facial expressions, lack of eye contacts during social interactions, and lack of joint attention skill; additional symptoms may include echolalia or an absence of verbalization (Koegel & Frea, 1993;Pierce & Schreibman, 1995).…”
Section: Introductionmentioning
confidence: 99%